2016
DOI: 10.1371/journal.pone.0161751
|View full text |Cite
|
Sign up to set email alerts
|

Yield, Esterification Degree and Molecular Weight Evaluation of Pectins Isolated from Orange and Grapefruit Peels under Different Conditions

Abstract: Orange (Citrus sinensis) and grapefruit (Citrus paradise) peels were used as a source of pectin, which was extracted under different conditions. The peels are used under two states: fresh and residual (after essential oil extraction). Organic acid (citric acid) and mineral acid (sulfuric acid) were used in the pectin extraction. The aim of this study is the evaluation the effect of extraction conditions on pectin yield, degree of esterification “DE” and on molecular weight “Mw”. Results showed that the pectin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
1
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(73 citation statements)
references
References 56 publications
(64 reference statements)
3
57
1
4
Order By: Relevance
“…High-intensity ultrasonic energy may destroy some chemical bonds of the polysaccharides, resulting in decarboxylation reaction [53,54]. Moreover, linear CSP molecules with galacturonic acid undergo different degrees of esterification, and the degree of esterification is high when the molecular volume is small [55]. Therefore, the content of -COOH in polysaccharides with low molecular weight (such as CSP4 and CSP5) decreases again Figure 13.…”
Section: Discussionmentioning
confidence: 99%
“…High-intensity ultrasonic energy may destroy some chemical bonds of the polysaccharides, resulting in decarboxylation reaction [53,54]. Moreover, linear CSP molecules with galacturonic acid undergo different degrees of esterification, and the degree of esterification is high when the molecular volume is small [55]. Therefore, the content of -COOH in polysaccharides with low molecular weight (such as CSP4 and CSP5) decreases again Figure 13.…”
Section: Discussionmentioning
confidence: 99%
“…As can be seen in Figures 3 and 4, the variation trend of DEc conforms with DEs with the alteration of independent variables. To summarize, the increasing of extraction temperature, time, and concentration of acid contributes to the low-ester pectin [36]. Figure 3(c) shows that the DEs changed more obviously at high extraction temperature than that at low extraction temperatures.…”
Section: Analysis Of Response Surfacementioning
confidence: 91%
“…Mw, DE, DM, and DA values As presented in Table 1, the Mw of natural sweet potato pectin was 7.53 × 10 5 g mol −1 , it was higher than that of grapefruit (1.54 × 10 5 -2.47 × 10 5 g mol −1 ) and orange pectin (1.639 × 10 5 -2.47 × 10 5 g mol −1 ), while lower than that of potato pectin (18.19 × 10 5 g mol −1 ). 13,16 The Mw of sweet potato pectin was decreased after modification, and the lowest Mw (0.05 × 10 5 g mol −1 ) was obtained by HHP-assisted E treatment, followed by E treatment (0.31 × 10 5 g mol −1 ). These results are comparable to those of previous studies, which showed that the Mw of sugar beet pulp pectin and potato pectin decreased upon application of HHP.…”
Section: Resultsmentioning
confidence: 99%